Managing heritage conservation projects in relation with quantity surveying profession: The case of Malaysia - Zolkafli, U.K.; Zakaria, N.; Sekak, S.N.A.A.; Rahmat, I. (University of Malaya, 2017)
Heritage buildings are deteriorating due to time, lack of care, high maintenance cost and lack of comprehensive guidelines and understanding on the management practices. Conservation is the only process that can protect heritage buildings from deterioration. Integrated teams of highly qualified professionals have to be involved in conservation of heritage buildings. As one o f the main players in heritage conservation projects, quantity surveyors should develop an in-depth knowledge of heritage buildings, conservation process, specifications and requirements by local and international authority. Therefore, the aim of this paper is to establish relationship o f heritage conservation and quantity surveyor competency. This aim is achieved through the following objectives; to identify the features o f heritage buildings, to identify the competency o f quantity surveyors in heritage building conservation projects and to establish relationships beUveen heritage conservation projects and quantity surveyors’ competency. Quantitative method was chosen for this study. The respondents were from the quantity surveyors who are registered with Board of Surveyors Malaysia and has experienced in building conservation project. SPSS (Descriptive Statistic) and PLS were used to analyze the data. Result showed that there is strong relationship between features of heritage building and quantity surveyors’ competency.